A relação entre a serpente e satã em Paradise Lost - Fernandes, Marcos Aurélio Zamith (2016)
This work aims at analyzing the character of Satan in the epic work Paradise Lost by the Puritan writer John Milton (1608-1674). More specifically, it aims at offering an answer to the question: in what manner do the traits of the serpent reflect Satan? In order to do that, the analysis was divided into parts. In the first chapter, it was presented the context of the literary production and reception of the work Paradise Lost in order to show features of this corpus and to relate them to other literary works and with its historical moment. In the second chapter, concepts of the narrative theory of Mieke Bal (1997) were applied to the protagonist so that the analysis of Satan in itself and in relation to other elements of the narrative was theoretically based. Finally, in the third chapter, based on a list of features provided by Charlesworth (2010) about the animal serpent (author's expertise), these features were related to the Milton's serpent so that one comprehends traits of the character of the serpent that together relate to Satan. This analysis is justified because many works were found about the Satan of Paradise Lost, nevertheless none whose theme was delimited in that manner. Once a narrative theory and texts from the literary criticism on Milton and of his epic poem pertinent to the current theme were chosen, it is expected that this dissertation allows the reader of Paradise Lost to acquire a more accurate view on the function of the character of Satan in the plot, particularly in the form of the tempting serpent assumed by Satan.